(untitled) (Nexo Revista Científica, 2020)
In order to investigate the effect of bacterial inoculation on yield, chlorophyll and protein content of alfalfa to obtain economically experimental products in Shahid Zande Rouh Agricultural Training Center in Kerman as a split plot in time based on a completely randomized block design with four replications on the ground Which had not been done before, was done. Bacterial inoculation was at three levels (Rhizobium meliluti, Rhizobium leguminasarum and no inoculation as a control). Bacterial inoculation had a significant effect on all studied traits and caused an increase in chlorophyll content, yield and protein percentage. In terms of fresh forage weight, the first and third crops had the highest yield with the application of Rhizobium meliloti (6 tons per hectare). The highest percentage of protein related to inoculation of Rhizobium meliloti was observed in the second Picking. According to the results of this study, inoculation with Rhizobium meliloti bacteria increases the ability of nitrogen fixation 3 to 4 times compared to the control and improved the alfalfa traits of Bami cultivar in southeastern Iran.